Plasmids 2015
DOI: 10.1128/9781555818982.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Rolling-Circle Replication

Abstract: 15 16 17 18 19 20 1. General aspects 21 2. The double-strand origin 22 3. The replication initiator Rep proteins 23 4. Control of rolling-circle replication24 4.1. Mechanisms for regulating synthesis of the Rep protein25 4.2. Mechanisms that restrict the use of Rep molecules to a single replication event 26 5. The single-strand origin 27 6. Host proteins involved in rolling-circle replication 28 6.1. Participation of DNA and RNA polymerases 29 6.2. Role of SF1 helicases and their interaction with the plasmid-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 175 publications
0
30
0
Order By: Relevance
“…The OD thus provides a rigid scaffold for the N- and C-terminal domains that need a certain level of conformational flexibility important for function 42 . In addition, we show that an OBD-OD hinge region may exist in viral Reps, which would confer the ability to process the DNA appropriately by facilitating the recognition of a variety of different DNA structures and topologies 15 43 . Moreover, severe distortion of the DNA might facilitate simultaneous binding of a Rep protein to all distant recognition sites in the origin DNA.…”
Section: Resultsmentioning
confidence: 94%
“…The OD thus provides a rigid scaffold for the N- and C-terminal domains that need a certain level of conformational flexibility important for function 42 . In addition, we show that an OBD-OD hinge region may exist in viral Reps, which would confer the ability to process the DNA appropriately by facilitating the recognition of a variety of different DNA structures and topologies 15 43 . Moreover, severe distortion of the DNA might facilitate simultaneous binding of a Rep protein to all distant recognition sites in the origin DNA.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, unlike most eukaryotic transposons and like prokaryotic RC transposons, Helitrons lacked terminal inverted repeats and target site duplications. RCR has been demonstrated for various prokaryotic phages and plasmids (Saleem, ; Ruiz‐Masó et al ., ). The prokaryotic initiator Rep protein plays a key role in RCR and the RepHel protein is postulated to play a similar role (Kapitonov and Jurka, ).…”
Section: Introductionmentioning
confidence: 97%
“…Within prokaryotes, Rep plays a central role in maintaining the plasmid copy number, as reported for the F plasmid in Escherichia coli (Kline, 1985). This regulation is also critical for the replication of plasmidderived, bacteriophage-like or virus-like DNA genomes (Ruiz-Masó et al, 2015). Reps are essential for the replication of multidrug-resistant bacteria in humans (Schumacher et al, 2014) and studies have suggested that Reps have a role in transmissible amyloid proteinopathy (Molina-García et al, 2018;Giraldo et al, 2016Giraldo et al, , 2011.…”
Section: Introductionmentioning
confidence: 98%